(untitled) (Circe de clásicos y modernos, 2021)
The experiences of transitional justice in Greek antiquity show to what extent emotions can play a specific role in the social reestablishment of memory, justice and truth. Based on a study of classical sources from Athens, Dikaia and Nakone, the purpose of this paper is to describe the affective fiction supporting this institutional framework: by expanding the emotional dimension from the realm of individuals to the society, a political installation of pathos is achieved with the aim of overcoming the traumatic effects of the civil war through the planning and design of an emotional community based on the virtues of reconciliation.